Models for the Sectoring-Arc Routing Problem (SARP) - Nunes, Ana Catarina; Mourão, Maria Cândida (ALIO-INFORMS 2010 - ALIO-INFORMS Joint International Meeting, 2010)
The Sectoring-Arc Routing Problem (SARP) models the activities associated with the streets of large urban areas, such as household waste collection. The SARP seeks to partition a mixed graph into a given number of smaller sub-graphs (sectors), and to build a set of trips in each sector. The objective is to minimize the total duration of the trips. Linear mixed integer programming formulations are presented for the SARP, and computational results over a set of benchmark problems are reported.